Testing small clutch size models with Daphnia. - Guinnee, M; West, SA; Little, T (2004)
Life-history theory predicts that for small clutches, variance in egg size (between individuals) should decrease in a predictable invariant manner as clutch size increases. To test this, we studied Daphnia magna at 350 different food treatments and recorded the number of eggs and the volume of each egg for their first clutch. As predicted, we found that the relationship between clutch size and resources devoted to reproduction was linear, variance in egg volume decreased with increasing clutch size, and resources were shared relatively equally between the eggs in a clutch. However, we found that the rate at which the range of egg volumes decreased with clutch size was slower than predicted. We discuss possible explanations for this discrepancy, including a lower limit on the volume of eggs that are produced and selection for smaller eggs when food is abundant. Consistent with this, we found that mean egg volume decreased with increasing clutch size.